Assessing alternatives for sustainability: Quantitative analysis in NEPA. (2nd January 2017) - Keys, David L.
ABSTRACT: This article proposes using an updated concept of sustainability that includes throughput, identifies tenets of sustainability already existing in the National Environmental Policy Act (NEPA) of 1969, and calls for the United States Environmental Protection Agency and the Council on Environmental Quality to promulgate jointly new regulations. These regulations would make the quantitative analysis of NEPA alternatives mandatory in an attempt to attain sustainability. Also discussed are the US EPA's efforts at incorporating sustainability into decision making.